(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
In South Asia, the fat female body is accorded narrative prominence to construct different synonyms of beauty and power. It is frequently consigned to the edges of fictional realms in visual representations and popular cultures. The standards of beauty (i.e., slender body, seductive dress, skin colour, make-up, etc.) are colonising the brains of women by dividing them and forcing them to adhere to the beauty norms by limiting their performance to the erotic subject. The article analyses the film Fanney Khan (2018) as an imperative study to understand how the concept of “fat body with ability” is subjugated to the conventional idea of “fat = inabilities, unhygienic, unhealthy, diseased and disabled” by the hegemonic society through the protagonist and eventually dismantling the same. This article investigates how juvenile fat subjects parley through numerous discursive interactions in the film Fanney Khan (2018). It illustrates how the female lead in the film confronts, resists and ultimately debilitates the conventional notions of the fat body and beauty standards. Although fatness is represented in this film as either a source of extreme animosity and conflict or a matter of desexualised femininity and conventional clothing choice, it nonetheless serves as a counter-hegemonic ideal that destabilises fatphobia (Singh 2021).